Drug‐Use Safety Enhancement Model—Theory and Application - Edward T. Dunbar Jr.; Ania Bartkowiak; Alison L. Brennan (Public Health Challenges)
ABSTRACT Harm reduction strategies mitigate the adverse effects of problematic drug use through overdose prevention, disease transmission reduction, and improved access to treatment resources. However, educational resources for safe drug use remain sparse and are predominantly focused on abstinence‐based approaches. This manuscript introduces the Drug‐Use Safety Enhancement Model (DUSEM), a comprehensive framework designed to foster informed and healthy relationships with drugs. Grounded in interdisciplinary research, DUSEM encompasses eight domains: knowledge, motivation, set (mindset), setting, dose, administration, recovery, and evaluation. Each domain offers practical strategies for educators, professionals, and drug consumers to enhance drug‐use safety. For the purpose of this analysis, “drugs” include all psychoactive substances regardless of whether they are legal in the United States. Our approach is rooted in the ethical, legal, and cultural practices common in the United States, particularly those related to best practices for providing care to people who use substances. The American context shaped how we understand and talk about drug use, which reflects the American reality of clinical practice in the fields of mental health and addictions. From the perspective of evaluation of the traditional, American conceptualization of the issues around drug use, our model's development acknowledges the need for a shift from outdated abstinence‐focused paradigms toward empowering individuals with informed practices for safer drug use. While serving as an educational guidepost, the model underscores the necessity for further research to refine its application, efficacy, and curriculum development. Helping professionals, such as teachers, counselors, social workers, and psychologists, can use this model in various educational, clinical, or institutional settings to help their audiences explore their own relationships with drugs. Ultimately, DUSEM aims to destigmatize drug use, foster healthier relationships with drugs, and improve safety for consumers.